Dormência de gemas sob influência da temperatura durante o período hibernal e resposta produtiva da macieira pelo uso de indutores de brotação - Hawerroth, Fernando José (2008)
Temperature is the main climate factor related to induction, maintenance and dormancy release in apple (Malus domestica Borkh.). The inadequate chilling exposure for this species causes the occurrence of budbreak problems, resulting in decrease in yield potential. Thus, the knowledge of physiological principles and environmental factors determining the dormancy phenomenon, especially winter temperature effects, it is necessary for the cultivars efficient selection in a productive region. Similarly cultural practices can be developed and adapted to minimize the problems cause by lack chilling during winter. The budbreak promoters application is one of main management s strategies used to decrease the problems of insufficient winter chilling on temperate fruit trees. Because the influence of budbreak promoters on plant s productive behavior, detecting this effects along of productive season became important. This study aimed to evaluate the budbreak and depth dormancy of apple cultivars exposed to different chilling conditions during the winter, and evaluate the apple productive response by budbreak promoters application. For this, three experiments were carried out in this research. In the first experiment, one-yearold twigs of Castel Gala and Royal Gala cultivars, grafted on M7 rootstock, were submitted to temperatures of 5, 10 and 15 C for different exposure periods (168, 336, 672, 1008 and 1344 hours). After treatments execution, the plants were kept in a greenhouse at 25ºC. Budbreak was quantified when accumulated 3444, 6888, 10332, 13776, 17220 and 20664 GDHºC after temperature treatments. The cultivars responded differently to temperature effect during the winter period. The temperature of 15 °C showed greater effectiveness on Castel Gala budbreak, while temperatures of 5 and 10ºC showed better performance in Royal Gala apple trees. It was not possible to estimate chilling requirement of cultivars studied through autumn grafted twigs, because the low budbreak obtained, derived of high apical dominance expressed by apple tree in this evaluation system. The objective of the second experiment was to evaluate the dormancy progression of apple cultivars with different chilling requirements. One-year-old twigs of Castel Gala , Condessa , Daiane , Fuji , Imperatriz and Royal Gala cultivars were exposed to 0, 336, 672, 1008 and 1344 chilling units at 4.5 ± 0.5 º C. After chilling exposure, the twigs were segmented into four cuttings (terminal, axillary superior, axillary median and axillary basal) and placed in growth chamber at 23±1ºC. The depth dormancy was measured by the mean time of budbreak (MTB). Through the method was not possible to group the cultivars according chilling requirement, indicating that correlation between the depth dormancy and chilling requirement isn t observed for all apple cultivars. In the third experiment were evaluated different hydrogen cyanamide and mineral oil combinations on phenology, budbreak and fruit production of Imperial Gala and Suprema s Fuji apple trees, during 2007/2008 growing season. Five budbreak promoters treatments were tested (1. control; 2. mineral oil 3.2%; 3. mineral oil 3.2% + hydrogen cyanamide 0.20%; 4. mineral oil 3.2% + hydrogen cyanamide 0.39%; 5. mineral oil 3.2% + hydrogen cyanamide 0.59%). The budbreak promoters application anticipated and reduced the blooming period, increasing the blooming overlap between Imperial Gala and Suprema´s Fuji cultivars. The budbreak promoters equalized and increased the budbreak in axillary and terminal buds, with the major budbreak level observed in Imperial Gala cultivar with 0.44% of hydrogen cyanamide and 3.2% of mineral oil treatment. The increase of hydrogen cyanamide concentration showed the tendency to decrease the fruit set. It was observed different treatment responses on production and mean fruit weight, probably to be related to fruit production predominance in different fructification structures.